PENERAPAN CONTEXTUAL TEACHING AND LEARNING DALAM MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN FIQIH: STUDI KUALITATIF NATURALISTIK DI MAN 8 JAKARTA TIMUR - Muqoramaturrahmah, Qori; Asiah, Siti (Turats, 2012)
The theme of this research on the Application of Contextual Teaching and Learning in Improving Student Achievement in Study of Fiqh (Islamic Jurisprudence): Naturalistic-Qualitative Studies in MAN 8 Jakarta Timur (East Jakarta). The application being used by teachers in the study of fiqh in Madrasah Aliyah Negeri 8 Jakarta Timur using the Contextual Teaching and Learning, frequently asked questions and a demonstration, the application is implemented by field of study Fiqh in order to achieve the objectives that have been formulated in the application of draft syllabus and implementation plan, which was designed by teachers in the study of fiqh before running the task of teaching. So, students are used to receive Contextual Teaching and Learning methods so that the application process to be effective because there is a supporting medium in accordance with the material presented.